2017
DOI: 10.1002/hep.29364
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of new direct antiviral agents in hepatitis C virus–infected patients with diffuse large B‐cell non‐Hodgkin's lymphoma

Abstract: The association of hepatitis C virus (HCV) with non-Hodgkin's lymphoma (NHL) has been demonstrated throughout the world. The new interferon-free direct antiviral agents (DAAs) showed high efficacy and safety, and preliminary data seem to confirm their activity on low-grade NHL. The question arises as whether or not-and how-to treat the HCV-positive patients suffering from diffuse large B-cell lymphomas (DLBCLs). The aim of this observational study was to evaluate whether DAA antiviral treatment of DLBCL/HCV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 43 publications
7
76
2
2
Order By: Relevance
“…Concerning concurrent DAAs and I-CT administration, none of the nine patients included in our study progressed or died at a median follow-up of 1.6 years (2-year OS and PFS of 100%), in line with remarkable results recently reported by Persico et al with the same concurrent approach [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Concerning concurrent DAAs and I-CT administration, none of the nine patients included in our study progressed or died at a median follow-up of 1.6 years (2-year OS and PFS of 100%), in line with remarkable results recently reported by Persico et al with the same concurrent approach [17].…”
Section: Discussionsupporting
confidence: 90%
“…The study demonstrated that HCV eradication with appropriate approved DAA regimens is feasible and also successful in a challenging population as HCV-positive DLBCL patients treated with I-CT, showing an SVR rate approaching 100% in all genotypes and negligible toxicity (no grade 3-4 AEs, few manageable grade 1-2 AEs, mainly related to RBV). Moreover, although on a small number of patients, we confirmed the absence of significant toxicity issues attributable to DAAs themselves or unexpected drug-drug interactions in patients treated concurrently with different widely adopted DAA regimens and I-CT, confirming the findings of the recently published pilot study evaluating contemporary administration of LDV-SOF and R-CHOP [17]. Compared to sequential strategy, the concurrent treatment with DAAs and I-CT exhibited the inherent advantage to be capable to prevent severe hepatic toxicity related to I-CT-induced HCV-RNA flares.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A sustained virological response and a lymphoproliferative disease response were obtained in 98% and 67%, respectively, of 45 patients with indolent B‐cell NHLs after completing a course of DAA therapy . Only few, but encouraging, studies have been published on DAA therapy in patients with B‐cell non‐Hodgkin lymphoma …”
Section: Impact Of Antiviral Hbv and Hcv Treatment On Development Of mentioning
confidence: 99%
“…Due to a lack of solid evidence of IFN‐free DAA regimens, the IFN‐based regimen can be considered in patients with NHL. Recent evidence shows that patients with DAA regimens also significantly improved in clinical outcomes, higher SVR rates, and prolonged disease‐free survival after NHL remission …”
Section: Treatment Of Hcv‐associated Ehms In 2018mentioning
confidence: 99%